Association of dietary intake, nutritional status and physical activity on sarcopenia in pre-elderly and elderly - Lestari Suryaningsih; Ani Margawati; Ahmad Syauqy (AcTion: Aceh Nutrition Journal, 2025)
Sarcopenia is a decrease in muscle mass, strength, and function, which has an impact on reducing physical performance and quality of life and is influenced by dietary intake and physical activity. This study aimed to analyze the relationship between diet, nutritional status, physical activity, and the incidence of sarcopenia.  A cross-sectional study was conducted in Simpati District, West Sumatra, from October to November 2024. The sample consisted of 167 pre-elderly individuals, and the elderly were selected through simple random sampling. Measurements included muscle and fat mass using a digital body composition scale, muscle strength using a handgrip dynamometer, dietary intake using the SQ-FFQ, physical activity using the GPAQ, waist circumference using a waist ruler, and physical performance assessed through the sit-to-stand test. Chi-square test and logistic regression were used for the analysis. Results: The prevalence rate of sarcopenia was 9,6%.  After adjusting for age and sex, waist circumference (p= 0,019; OR= 4,2) was associated with sarcopenia, while after adjusting for age, physical activity (p= 0,016; OR= 4,5), and waist circumference (p= 0,042; OR= 3,3) were associated with sarcopenia. After adjusting for sex, energy intake (p= 0,050; OR= 3,1), physical activity (p= 0,006; OR= 5,7), and waist circumference (p= 0,007; OR= 4,8) were associated with sarcopenia. Conclusion: Energy intake, physical activity, and waist circumference were associated with sarcopenia in elderly and pre-elderly individuals. Appropriate nutritional intervention, increased physical activity, and waist circumference monitoring are essential for sarcopenia management.